Biological Components and Bioelectronic Interfaces of Water Splitting Photoelectrodes for Solar Hydrogen Production. Issue 11 (11th December 2014) - Braun, Artur; Boudoire, Florent; Bora, Debajeet K.; Faccio, Greta; Hu, Yelin; Kroll, Alexandra; Mun, Bongjin S.; Wilson, Samuel T.
Abstract Artificial photosynthesis (AP) is inspired by photosynthesis in nature. In AP, solar hydrogen can be produced by water splitting in photoelectrochemical cells (PEC). The necessary photoelectrodes are inorganic semiconductors. Light‐harvesting proteins and biocatalysts can be coupled with these photoelectrodes and thus form bioelectronic interfaces. We expand this concept toward PEC devices with vital bio‐organic components and interfaces, and their integration into the built environment.